2010
DOI: 10.1016/j.landusepol.2009.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of agricultural land rental market transactions in Bangladesh

Abstract: a b s t r a c tLand rental market transactions have been the norm in land scarce rural Bangladesh mainly due to the inadequacies of the governmental land distribution system to meet the growing demand for land and to correct imbalances in factor proportions at the farm-level. The present study jointly determines the socioeconomic factors underlying decision to rent-in land and/or rent-out land by the Bangladeshi farmers in the land rental market using a bivariate Tobit model. The model diagnostic reveals that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 20 publications
3
39
2
Order By: Relevance
“…Another socioeconomic factor which determines land rent trends is the quality of the land. Rahman (2010) showed that farmers are more willing to rent land when the land is fertile in order to increase their agricultural output. This coincides with the findings from this study, where differences can be seen between Shobna and Faltita soil quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another socioeconomic factor which determines land rent trends is the quality of the land. Rahman (2010) showed that farmers are more willing to rent land when the land is fertile in order to increase their agricultural output. This coincides with the findings from this study, where differences can be seen between Shobna and Faltita soil quality.…”
Section: Resultsmentioning
confidence: 99%
“…Salinity intrusion in rivers and canals has limited the access people have to freshwater bodies, reducing agricultural productivity (Afroz and Alam, 2010). Furthermore, saline intrusion is widely considered to have a negative impact on agriculture, reducing plant growth and decreasing productivity (Rahman, 2010). There is often a premise that SLR drives salt water intrusion further inland, and many studies have highlighted the reduced capacity for farmers to engage in agriculture when salinity levels are high (Deb, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, more than 70% of farmers did not participate in land use transfer. The proportion of non-participation remained high compared to corresponding estimates of 54% in India and 37% in Bangladesh [4,5]. Why is the proportion of land in circulation in China still on the low side?…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 89%
“…9 Among others, Barbier (1990), Barbier and Bishop (1995) and Grepperud (1997) use similar production functions. 10 This assumption is realistic especially for the case of Bangladesh, where, albeit very low per-capita farm size, fertile land contributes to higher rice productivity (Rahman 2010). 11 Bulte and van Soest (2001) assume that rural households can indirectly enhance the regeneration of natural capital (i.e., topsoil in our model) by allocating a part of their labor time for conservation.…”
Section: 10mentioning
confidence: 99%
“…14 However, because tenure security is defined in terms of owned-operated and rented-operated land, it is likely to be endogenous in terms of household characteristics (e.g., gender, age and schooling of the household head and composition of the household), access to agricultural assets (e.g., plough ownership) and dependency on agriculture (e.g., landholding and primary occupation) (Taslim and Ahmed 1992;Rahman 2010;Eskander and Barbier 2016). In other words, the size of owned land may be exogenously determined, but overall operated land will include rented land, the volume of which is likely to be endogenously determined within the system of equations determining the operated land and farming decisions of the household.…”
Section: Deininger and Jin 2006)mentioning
confidence: 99%